Habitat Utilization by Bobwhite Quail During Winter - Noel S. Yoho; Ralph W. Dimmick (National Quail Symposium Proceedings, 2017)
This study was conducted on a 214-acre area of the Ames Plantation, Fayette County, Tennessee. Information on habitat utilization by bobwhite quail (Colinus virginianus) during winter was obtained by telemetering quail during January - March, 1970. The ranges of five coveys averaged 16.7 acres. Coveys spent little time in cultivated fields although this type of cover constituted much of the home ranges of 4 coveys. Cedar woods, hardwood forests, and old fields were used in proportion to their abundance for diurnal protective cover by the quail population, but presence of honeysuckle (Lonicera japonica) or other dense understory cover generally increased the attractiveness of a wooded area for quail. Honeysuckle was also the preferred ground cover for roosts.